Outcomes following watchful waiting for stage II–IV follicular lymphoma patients in the modern era. (5th January 2016) - Nastoupil, Loretta J.; Sinha, Rajni; Byrtek, Michelle; Ziemiecki, Ryan; Zhou, Xiaolei; Taylor, Michael; Friedberg, Jonathan W.; Link, Brian K.; Cerhan, James R.; Dawson, Keith; Flowers, Christopher R.
Summary: To examine the effectiveness of an initial management strategy of watchful waiting for follicular lymphoma (FL) in clinical practice, we compared outcomes for patients diagnosed 2004–2007 in the United States initially managed with watchful waiting with outcomes following initial rituximab monotherapy and chemoimmunotherapy. In total, 1754 stage II–IV patients in the National LymphoCare Study underwent watchful waiting ( n  =   386), rituximab monotherapy ( n  =   296) or rituximab plus chemotherapy ( n  =   1072) as initial management strategy. Female patients and those who received treatment in the Northeast or in an academic setting more commonly underwent watchful waiting versus initial chemoimmunotherapy; whereas patients with grade 3 histology, anaemia, elevated lactate dehydrogenase, extranodal involvement, B symptoms or performance status ≥1 more commonly received chemoimmunotherapy. Although time to new treatment and progression‐free survival following first‐ and second‐line therapy were improved with chemoimmunotherapy, and time to chemotherapy was improved with rituximab monotherapy, there were no differences in overall survival between watchful waiting and chemoimmunotherapy or rituximab monotherapy. With 8‐year overall survival estimates of 74%, initial management with watchful waiting in the context of sequential therapy remains a viable option for FL patients in the modern era. This trial was registered atwww.clinicaltrials.gov (NCT00097565).